Clinical management and treatment of snakebite accidents in a hospital in Bolivia - Acuña Rodriguez, Danitza Adriana (2025)
Objective: To analyze the initial clinical management of patients with snakebites in a hospital in Bolivia. Methods: A quantitative, descriptive, and retrospective study was conducted at the Hospital San Francisco de Asís in Villa Tunari, Cochabamba. A total of 144 medical records of patients diagnosed with snake venom poisoning between January 1, 2022, and June 30, 2023, were included. Data on age, gender, signs and symptoms, type of snake, use of a tourniquet, antivenom, antibiotics, analgesics, and length of hospital stay were collected. Descriptive analysis was used to evaluate the data. Results: Most patients were women (51 %) with an adult age range (27 to 59 years). A tourniquet was applied in 9.7% of the cases. The predominant signs and symptoms were pain (90 %) and edema (70 %). Tramadol was the most commonly used analgesic (39 %) and cloxacillin the most frequently used antibiotic (45 %). The BothropsLachesis Antivenom was administered in 62% of the cases. Sixty percent of patients did not experience complications, and the average length of hospital stay was 4 days. Conclusions: This study highlights the importance of standardized and timely clinical management in snakebite cases, emphasizing the correct identification of the venom, pain management, rational use of antibiotics, and proper administration of the specifc antivenom.